Bilateral occipital extradural hematoma in a child - Pandey, Sharad (J Pediatr Neurosci, 2015)
Extradural hematoma (EDH) occurs in approximately 2% of all patients with head injuries. Bilateral EDHs account for 2–10% of all acute EDHs in adults but are exceedingly rare in children. Posterior fossa EDHs occurs in 5% of all cases of EDHs. EDHs in children are more frequently venous (from tears of a dural sinus or diploic veins) and consequently have a better prognosis than EDHs in adults. Once the diagnosis of BEH is confirmed, urgent surgical treatment should be considered. We are reporting such rare form of injury as bilateral occipital EDH with supratentorial extension in 12 years child following road traffic accident.